2012
DOI: 10.1021/bi300830q
|View full text |Cite
|
Sign up to set email alerts
|

Functional Modular Dissection of DEBS1-TE Changes Triketide Lactone Ratios and Provides Insight into Acyl Group Loading, Hydrolysis, and ACP Transfer

Abstract: The DEBS1-TE fusion protein is comprised of the loading module, the first two extension modules, and the terminal TE domain of the Saccharopolyspora erythraea 6-deoxyerythronolide B synthase. DEBS1-TE produces triketide lactones that differ on the basis of the starter unit selected by the loading module. Typical fermentations with plasmid-based expression of DEBS1-TE produce a 6:1 ratio of propionate to isobutyrate-derived triketide lactones. Functional dissection of the loading module from the remainder of DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Combinatorial NRPS/PKS systems have enabled predictable changes to the scaffold core, derived from three programmable inputs into the biosynthesis. The inputs include the following: 1) variable use of organic building blocks such as short-chained acyl-coenzyme A (CoA) molecules or amino acids for the chain elongation step of scaffold synthesis 61 , 63 68 ; 2) chain length variations originating from KS and TE engineering 69 70 ; and 3) alterations in the reduction program of the scaffold as a result of DH, KR, and ER engineering 71 72 . Yan et al exemplified the biosynthetic potential to diversify antimycin (ANT) scaffolds through the metabolic engineering of promiscuous NRPS/PKS enzymes in the ANT-producing Streptomyces sp.…”
Section: Engineering Small Molecule Discovery Platforms: Derivatizatimentioning
confidence: 99%
“…Combinatorial NRPS/PKS systems have enabled predictable changes to the scaffold core, derived from three programmable inputs into the biosynthesis. The inputs include the following: 1) variable use of organic building blocks such as short-chained acyl-coenzyme A (CoA) molecules or amino acids for the chain elongation step of scaffold synthesis 61 , 63 68 ; 2) chain length variations originating from KS and TE engineering 69 70 ; and 3) alterations in the reduction program of the scaffold as a result of DH, KR, and ER engineering 71 72 . Yan et al exemplified the biosynthetic potential to diversify antimycin (ANT) scaffolds through the metabolic engineering of promiscuous NRPS/PKS enzymes in the ANT-producing Streptomyces sp.…”
Section: Engineering Small Molecule Discovery Platforms: Derivatizatimentioning
confidence: 99%
“…With the introduction of a reductive loop swap, the chimeric enzymes would programmatically produce 2,4-dimethyl pentanoic acid. As in vitro PKS studies have shown divergence from in vivo results 24,25 due to underestimation of factors including limiting substrate, crowding, and solubility, 26 we cloned ten chimeric modules into an E. coli -Streptomyces albus shuttle vector and conjugated it into Streptomyces albus J1074 ( Table S1 ). 27 Following ten-day production runs in a rich medium, cultures of Streptomyces albus harboring each of the constructs were harvested and the supernatants were analyzed with LC-MS for product levels.…”
Section: Resultsmentioning
confidence: 99%
“…While in the native Saccharopolyspora erythrea DEBS is primed exclusively by propionyl-CoA [196] , the LM of DEBS incorporates other priming units in heterologous systems [197] . Depending on the host, TKLs from DEBS1+TE can form via priming by acetyl-CoA (in S. coelicolor [198] and S. venezuelae [197] ) or isobutyryl-CoA (in S. venezuelae [197] ), albeit as minor products. Reynolds and coworkers interrogated the relationship between PKS architecture and starter unit incorporation in variations of DEBS1+TE expressed in S. venezuelae .…”
Section: Host Precursor and Protein Engineering Synergymentioning
confidence: 99%
“…When the loading domain is placed on a separate polypeptide from module 1, there is a resulting kinetic stall. This kinetic stall shifts the product formation towards thermodynamic control, especially when higher levels of isobutyl-CoA are present [197] . This example demonstrates that the apparent selectivity of PKS domains can be altered depending on the architecture of the PKS in concert with the precursor availability.…”
Section: Host Precursor and Protein Engineering Synergymentioning
confidence: 99%